Možnosti razvoja nepremičninskega davčnega sistema v Sloveniji - Mitrović, Dušan (Geodetski vestnik, 1999)
On the basis of current state of affairs, an opinion for the possible development of real estate tax system in Slovenia is presented, where the institutional, managing and technological aspects are mostly discussed
Keywords: davčni sistemi; davki; nepremičnine; razvoj; Slovenija